Results of analytical design of autopilot of transport aircraft in cruise flight mode - Кривоносенко, О. П.; Сущенко O A.; Юрченко, О. М. (Proceedings of National Aviation University (archive), 2020)
Dynamic design of the channel of stabilization of the pitch of a heavy transport aircraft in a horizontal flight is performed, taking into account random perturbing factors and obstacles to meters. The change of the index of quality and parameters of the optimum stabilization system depending on the operating situation of the flight is studied.